Comparison of platelet rich fibrin and collagen as osteoblast‐seeded scaffolds for bone tissue engineering applications. Issue 3 (1st November 2011) - Gassling, Volker; Hedderich, Jürgen; Açil, Yahya; Purcz, Nicolai; Wiltfang, Jörg; Douglas, Timothy
Abstract Objectives The loss of jaw bone caused by different kinds of pathologies leads to dysfunction and reduced quality of life in affected patients. Thus, the pivotal goal in bone tissue engineering is to reconstruct these defects. The essential precondition for new tissue generation is an extracellular matrix which acts as a scaffold so that cells can migrate, differentiate, and proliferate. Fibrin, a biopolymer responsible for blood clot formation, has been shown to be suitable for tissue engineering applications. The aim of the present study is a comparison of platelet rich fibrin (PRF) with the commonly used collagen membrane BioGide® as a scaffold for human osteoblast cell seeding for bone tissue engineering. Material and methods Human osteoblasts were cultured with eluates from PRF (n = 7) and BioGide® (n = 8) membranes incubated in serum‐free cell culture medium. Vitality of these cells was assessed by fluorescein diacetate and propidium iodide staining, biocompatibility with the lactate dehydrogenase test and proliferation levels with the MTT ([3‐(4, 5‐Dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium‐bromide]), and BrdU (5‐bromo‐2‐deoxyuridine) tests. In addition, human osteoblasts were seeded on both membrane systems and cell growth was compared by the water soluble tetrazolium (WST‐1) (4‐[3‐(4‐iodophenyl)‐2‐(4‐nitrophenyl)‐2H‐5‐tetrazolio]‐1, 3‐benzene disulfonate) test and scanning electron microscopy (SEM). Osteoblastic differentiation was assessed by alkaline phosphatase activity measured by ELISA in the supernatant of osteoblasts cultivated on PRF membranes (n = 10), PRF clots (n = 10), and BioGide® membranes (n = 10). Results Lactate dehydrogenase test values were higher for PRF compared to BioGide®. The BrdU test showed superior cell growth after cultivation in eluate from PRF than in eluate from BioGide®. The WST‐1 assay demonstrated superior cell proliferation on PRF than on BioGide®. SEM revealed osteoblast colonization of both membranes. Cultivation of osteoblasts on PRF membranes and PRF clots showed significantly higher alkaline phosphatase activity than on BioGide® membranes. Conclusion Metabolic activity and proliferation of human osteoblast cells in vitro were supported to a significant higher extent by eluates from PRF membranes. Both membranes are suitable as scaffolds for cultivation of human osteoblast cells in vitro; proliferation was significant higher on PRF membranes and on PRF clot than on BioGide® membranes.